Tax Compliance Challenges Among Legal Practitioners in Nigeria: Tantangan Kepatuhan Pajak di Kalangan Praktisi Hukum di Nigeria - Omozue, Moses Ogorugba (Indonesian Journal of Law and Economics Review, 2025)
General Background: Tax compliance is a fundamental obligation for income-earning professionals, including lawyers. Specific Background: In Nigeria, the taxation of legal practitioners has sparked debate, particularly concerning the classification of legal practice and the fairness of related tax policies. Knowledge Gap: Despite existing legal frameworks, gaps in awareness, enforcement, and consistency in tax administration persist among Nigerian lawyers. Aims: This study examines the tax obligations of Nigerian legal practitioners, analyses statutory provisions including the Personal Income Tax Act (PITA), Capital Gains Tax Act (CGTA), and Value Added Tax Act (VATA), and compares practices with jurisdictions such as the United Kingdom, the United States, and South Africa. Results: Findings reveal systemic compliance challenges, low awareness, and administrative inconsistencies that hinder effective taxation of legal professionals. Novelty: The paper offers a unique doctrinal analysis linking statutory interpretation with comparative international insights to recommend profession-specific reforms. Implications: The study underscores the need for clearer tax policies, targeted legal education reforms, and the adoption of digital tax-filing systems to enhance compliance, support law firm sustainability, and strengthen government revenue generation. Highlights: Tax Challenges: Nigerian lawyers face low awareness and inconsistent tax administration. Comparative Analysis: Insights from the UK, US, and South Africa reveal best practices. Policy Recommendations: Calls for legal education reform and digital tax-filing systems. Keywords: Taxation, Legal Practitioners, Tax Compliance, Law Firms, Economic Impact